2013
DOI: 10.1007/s00268-013-2065-y
|View full text |Cite
|
Sign up to set email alerts
|

Learning Tools and Simulation in Robotic Surgery: State of the Art

Abstract: Robotic surgery has emerged as a new technology over the last decade and has brought with it new challenges, particularly in terms of teaching and training. To overcome these challenges, robotic courses, virtual simulation, and dual consoles have been successfully introduced. In fact, there are several simulators currently on the market that have proven to be a valid option for training, especially for the novice trainee. Robotic courses have also found success around the world, allowing participants to implem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 121 publications
0
16
0
2
Order By: Relevance
“…This can be done either by more classic virtual reality, or utilizing more advanced augmented reality techniques. Several platforms currently exist that support virtual-reality training [4,5,7,20,21,24,41]. Initial validation studies of virtual-reality training in robotic surgery show encouraging results [6,16,19,23,25,41]; however, these platforms are yet to be fully validated for both basic-skill and procedural trainings.…”
Section: Pss Has Potential To Play An Important Role In Robotic Trainmentioning
confidence: 96%
“…This can be done either by more classic virtual reality, or utilizing more advanced augmented reality techniques. Several platforms currently exist that support virtual-reality training [4,5,7,20,21,24,41]. Initial validation studies of virtual-reality training in robotic surgery show encouraging results [6,16,19,23,25,41]; however, these platforms are yet to be fully validated for both basic-skill and procedural trainings.…”
Section: Pss Has Potential To Play An Important Role In Robotic Trainmentioning
confidence: 96%
“…Even with a relative paucity of published reports on robotic simulators, and the lack of study in favor of one simulator over another, the trend is clearly in favor of virtual training [107]. Currently there are four commercially available simulators.…”
Section: Robotic Simulatorsmentioning
confidence: 99%
“…Various societies for robotic surgery are currently at work on a clear curriculum for the new generation of robotic surgeons, which hopefully will lead to standardization [107]. Trainees recognize the benefit of simulation training a questionnaire based study of a group of American urologic association trainees concluded Trainees believe that the simulator replicates real-life robotic console movements and almost all believe they would be benefit from having access to robotic simulation [108].…”
Section: Robotic Simulatorsmentioning
confidence: 99%
“…One study demonstrated that set up and operative times significantly decrease as surgeons and staff became more familiar with the equipment and performed more cases 24 . By encouraging surgeons to enrol in the available robotic training programs or to practice with robotic simulation consoles, operating times and complication rates are expected to decrease [25][26][27] .…”
Section: Current Uses Of Robotics In Medicinementioning
confidence: 99%